2011
DOI: 10.1158/0008-5472.can-10-3764
|View full text |Cite
|
Sign up to set email alerts
|

CCL11–CCR3 Interactions Promote Survival of Anaplastic Large Cell Lymphoma Cells via ERK1/2 Activation

Abstract: CCR3 is a specific marker of anaplastic large cell lymphoma (ALCL) cells. ALCL cells also express CCL11, a ligand for CCR3, leading to the hypothesis that CCL11 may play an autocrine role in ALCL progression. In this study, we investigated a role of CCL11 in cell survival and growth of human Ki-JK cells, established from an ALCL patient, and murine EL-4 lymphoma cells. Both Ki-JK and EL-4 cells expressed cell surface CCR3. CCL11 increased cell survival rates of Ki-JK cells in a dose-dependent manner, whereas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
(61 reference statements)
6
37
0
1
Order By: Relevance
“…Previous studies showed that the binding between CCL11 and CCR3 upregulated the expressions of VEGF, IL-8, PDGF-BB, and FGF [810]. In addition, it also induced phosphorylation of ERK1/2, MEK1 and STAT3 [5, 29]. Accordingly, CCL11 could act as: (1) an inflammatory chemokine contributing to the host response to neoplasia, (2) a proangiogenic factor promoting new vessel formation, (3) a general pro-inflammatory factor in response to tissue stress and/or necrosis, and/or (4) an autocrine growth factor released by cancer cells to promote proliferation, migration, and invasion [5, 8, 30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that the binding between CCL11 and CCR3 upregulated the expressions of VEGF, IL-8, PDGF-BB, and FGF [810]. In addition, it also induced phosphorylation of ERK1/2, MEK1 and STAT3 [5, 29]. Accordingly, CCL11 could act as: (1) an inflammatory chemokine contributing to the host response to neoplasia, (2) a proangiogenic factor promoting new vessel formation, (3) a general pro-inflammatory factor in response to tissue stress and/or necrosis, and/or (4) an autocrine growth factor released by cancer cells to promote proliferation, migration, and invasion [5, 8, 30].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely expressed in human tissues including heart, colon, kidney, small intestine, lung, pancreas, liver, and ovary [3, 4]. CCL11 primarily binds to CCR3, a seven-transmembrane-domain G-protein-coupled chemokine receptor [5]. This binding triggers a series of signal transduction events involving transient release of intracellular calcium, cytoskeletal rearrangements, generation of inositol triphosphate, activation of protein kinase C and prolonged receptor internalization into an endocytic compartment [57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In anaplastic large cell lymphomas, the CCR3/CCL11 interaction promotes tumor cell proliferation and inhibits apoptosis through ERK1/2, Bcl-xL and the production of survivin [192]. Similarly, through an AKT signaling pathway, CCR7 and its ligands CCL19 and CCL21 induce squamous cell carcinoma of the head and neck growth in vitro and in vivo [230].…”
Section: The Role Of Chemoattractant Gpcrs Expressed By Tumor Cellsmentioning
confidence: 99%
“…After first-line chemotherapy, 15-20% of patients do not respond to its treatment; the short-and long-term toxicity of chemotherapy continues to adversely impacting the long-term prognosis of patients with lymphoma, making it important to explore strategies. Both T lymphoma and B lymphoma have active MEK/ERK (Chapuy et al, 2011;Miyagaki et al, 2011;Martin-Sanchez et al, 2013). Active ERK1/2 can phosphorylate a variety of substrates to promote cell proliferation, motility, and survival (Karin et al, 1997;Mebratu and Tesfaigzi, 2009;Roskoski, 2012;Courcelles et al, 2013).…”
Section: Introductionmentioning
confidence: 99%